Profile of Secondary Glaucoma in a Tertiary Eye Hospital of Eastern Nepal - Gurung, Jamuna; Sitoula, Rakshya Pant; Singh, Anjani Kumar (Nepalese Journal of Ophthalmology, 2021)
Background: To determine the clinical profile and causes of various types of secondary glaucoma.Materials and methods : This was a hospital-based cross-sectional study conducted in a tertiary eye hospital of eastern Nepal from 1st June to 30th November, 2017. Patients who met the criteria for secondary glaucoma underwent detailed ophthalmic examination.Results : Out of 7079 patients diagnosed with glaucoma or glaucoma suspects, 528 (7.4%) had secondary glaucoma. The mean age at presentation was 52 ± 17 years with male to female ratio of 1.5:1. The most common cause was lens induced 173 (32.8%) followed by neovascular 107 (20.3%), steroid induced 86 (16.3%), traumatic 76 (14.4%), post-vitrectomy 17 (3.2%), uveitic 11 (2.1%), pseudophakic 10 (1.9%), aphakic 8 (1.5%), post-keratoplasty 5 (0.9%) and miscellaneous included 35 (6.6%). Post-traumatic 31 (29.5%) was more prevalent below 41 years while lens induced glaucoma 86 (49%) above 60 years of age. At presentation, the average IOP was 40 ± 11 mmHg. 36 (6.8%) had no light perception in the presenting eye and a large number of participants 307 (58.1%) presented with visual acuity of